Squamous-cell carcinoma of the lower lip: a retrospective study of 58 patients - Santos, Luiz Roberto Medina dos; Cernea, Cláudio Roberto; Kowalski, Luiz Paulo; Carneiro , Paulo Carneiro; Soto, Miriam Nakagami; Nishio, Sunao; Hojaij, Flávio Carneiro; Dutra Jr., Augusto; Silva Filho, Gilberto Britto e; Ferraz, Alberto Rossetti (São Paulo Medical Journal, 1996)
The charts of 58 patients with squamous-cell carcinomas of the lower lip, treated at the General Hospital of the University of São Paulo Medical School from January 1980 to December 1989, were retrospectively analyzed. In addition to regular demographic data, all available information was collected regarding: smoking and drinking habits; sun exposure; clinical stage; macroscopic features of the primary lesions; type of treatment; and follow-up. A meticulous pathological analysis, comprising the histologic differentiation grade, maximal tumor thickness, sun elastosis, perineural spread, vascular and muscular invasion, surgical margins, peritumoral inflammatory infiltrate, and positive lymph nodes, with or without extracapsular spread, was undertaken as well. The evaluation of the overall 5-year survival showed significant statistical differences, with prognostic implications, for the following variables: maximal tumor thickness, T-stage and positive nodes.